Survival Analysis of Covid-19 Patients Based on Time of Recovery - Rina Widyasari; Muhammad Chairul Imam; Ramya Rachmawati; Rina Filia Sari (Jurnal Matematika, Statistika dan Komputasi, 2022)
Corona virus is a virus that can cause the respiratory tract to become infected, and this viral infection is called COVID-19. This virus spreads so fast that it has spread to several countries, including Indonesia. In Indonesia, COVID-19 was detected in early March, precisely on March 2, 2020. The uncertain increase in the number of COVID-19 patients will have an impact on society and the country. This condition is compounded by the high number of deaths due to the COVID-19 virus. Therefore, this study was conducted to analyze survival based on the healing rate of COVID-19 patients, in order to obtain information about the time period and the factors that cause a person with COVID-19 to survive. The method used in the survival analysis is the Kaplan-Meier test as a counter to the estimated recovery time of COVID-19 patients and the Log-Rank test to test for differences in the survival function of the recovery time of COVID-19 patients in the two groups. Kaplan-Meier and Log-Rank tests are part of the non-parametric method which is a statistical test that does not require any assumptions about the distribution of population data. The data used is data on COVID-19 patients at the Malahayati Hospital from January to May 31, 2021. The conclusion obtained is the survival function curve / length of time on the recovery rate of COVID-19 patients based on gender, age, and positive and suspected COVID-19 patients. with and without comorbidities. However, based on the Log-Rank test with = 0.05, it was concluded that there was no significant difference in the length of time for recovery of COVID-19 patients based on gender, age and positive patients and patients with suspected COVID-19 with comorbid and without comorbidities.